A Straightforward Approach to Tetrahydroindolo[3, 2‐b]carbazoles and 1‐Indolyltetrahydrocarbazoles through [3+3] Cyclodimerization of Indole‐Derived Cyclopropanes. Issue 4 (6th August 2015) - Ivanova, Olga A.; Budynina, Ekaterina M.; Khrustalev, Victor N.; Skvortsov, Dmitriy A.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract: A rapid new approach to produce biologically relevant bisindoles, namely indolyltetrahydrocarbazoles and indolo[3, 2‐ b ]carbazoles, has been developed, based on the Ga(OTf)3 ‐catalyzed [3+3] cyclodimerization of indole‐derived donor–acceptor cyclopropanes. Chemoselectivity of the process depends on the location of the three‐membered ring at the indole core. Abstract : Gemination for creation : A new method for bisindole assembly was proposed through [3+3] cyclodimerization of indole‐derived cyclopropanes. Variations in the cyclopropane position at the indole core fine‐tune the process towards the selective formation of indolyltetrahydrocarbazoles or indolo[3, 2‐ b ]carbazoles.